Plastef, a code for the numerical simulation of thermoelastoplastic bahaviour of materials using the finite element method - Basombrio, F.G.; Sanchez Sarmiento, Gustavo (1978)
Fil: Basombrio, F.G. Comisión Nacional de Energía Atómica; Argentina